2021
DOI: 10.3389/fmicb.2021.645362
|View full text |Cite
|
Sign up to set email alerts
|

Larval Diet Abundance Influences Size and Composition of the Midgut Microbiota of Aedes aegypti Mosquitoes

Abstract: The midgut microbiota of the yellow fever mosquito Aedes aegypti impacts pathogen susceptibility and transmission by this important vector species. However, factors influencing the composition and size of the microbiome in mosquitoes are poorly understood. We investigated the impact of larval diet abundance during development on the composition and size of the larval and adult microbiota by rearing Aedes aegypti under four larval food regimens, ranging from nutrient deprivation to nutrient excess. We assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…albopictus. Bacterial growth in rearing water depends on the strain and diet considered although total bacterial load increases with diet concentration (43, 46). Maintenance of a bacterial homeostasis in mosquitoes is under tight immunological control (65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…albopictus. Bacterial growth in rearing water depends on the strain and diet considered although total bacterial load increases with diet concentration (43, 46). Maintenance of a bacterial homeostasis in mosquitoes is under tight immunological control (65).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that diet concentration impacts microbiota composition in Ae. aegypti larvae and adults (46). Our results unravelled a more complex interaction involving both the diet concentration and the bacterial load inoculum in shaping bacterial communities in larval water.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti mosquitoes in comparison to large mosquitoes while fecundity was decreased in the former suggesting that in small size mosquitoes, the blood-meal was predominantly processed for nutrient supply rather than diverted for egg development [ 33 ]. In addition, the midgut microbiome in adult mosquitoes has been shown to be altered by restricting the larval diet [ 34 ]. This, in turn, can impact midgut infection of arboviruses; for instance, a microbial metalloprotease secreted by Serratia marcescens increased the susceptibility of the Ae .…”
Section: Discussionmentioning
confidence: 99%
“…qPCR: To assess the total amount of bacteria in each tissue sample, we conducted qPCR targeting the 16S rRNA gene as described in [35]. Briefly, each reaction contained 7.5 μL SYBR master mix (Applied Biosystems), 0.35 μL of each primer (primer starting concentrations were all 10 μM), 5 μL template (diluted 1:20), and MilliQ water to a final volume of 15 μL.…”
Section: Culture-independent Experimentsmentioning
confidence: 99%
“…High-throughput 16S amplicon sequencing and data processing: High-throughput 16S amplicon sequencing was performed as described in [35] at the Microbial Analysis, Resources, and Services center at the University of Connecticut. Briefly, 5ng of DNA was used as template in a PCR with 515F and 806R primers with Illumina adapters and eight basepair dual indices [37,38].…”
Section: Culture-independent Experimentsmentioning
confidence: 99%